Dự thảo Nghị quyết về Kế hoạch tài chính quốc gia và vay, trả nợ công 5 năm giai đoạn 2021 - 2025 - Quốc hội (2021)
Toàn văn Dự thảo Nghị quyết về Kế hoạch tài chính quốc gia và vay, trả nợ công 5 năm giai đoạn 2021 - 2025